2009
DOI: 10.1590/s1678-77572009000700007
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the dentin-pulp complex in teeth submitted to orthodontic movement in rats

Abstract: In order to microscopically analyze the pulpal effects of orthodontic movement, 49 maxillary first molars of rats were submitted to orthodontic appliance composed of a closed coil spring anchored to the maxillary incisors, placed for the achievement of mesial movement. Material and Methods: Ten animals were used as the control group and were not submitted to orthodontic force; the other animals were divided into groups according to the study period of tooth movement, namely 1, 2, 3, 4, 5, 6 and 7 days. The inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…These authors found higher root resorptions associated with CF, corroborating data that duration plays an important role in the biological mechanism, promoting different tissue reactions. 1 Massaro, et al 19 (2009) observed higher radicular resorption at day 7 of ITM with continuous force; however, without greater pulp damage. Further studies are needed to investigate whether radicular resorption can be associated with pulp alterations in later periods after tooth movement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These authors found higher root resorptions associated with CF, corroborating data that duration plays an important role in the biological mechanism, promoting different tissue reactions. 1 Massaro, et al 19 (2009) observed higher radicular resorption at day 7 of ITM with continuous force; however, without greater pulp damage. Further studies are needed to investigate whether radicular resorption can be associated with pulp alterations in later periods after tooth movement.…”
Section: Discussionmentioning
confidence: 99%
“…Histological images were captured using an optical light microscope (Carl Zeiss, Göttingen, Germany), coupled to a digital camera (Axio Cam MRc5, Carl Zeiss, Göttingen, Germany). The radicular pulp of five roots of the right first molar ( Figure 3 ) was evaluated following an adaptation of the method proposed by Massaro, et al 19 (2009). The following histological characteristics were evaluated: presence or absence of inflammatory infiltrate, reduced cellularity, increased fibrosis, pulp hyalinization, pulp nodules, diffuse calcification, necrosis, vascular congestion, hemorrhage, thrombosis, reactional dentin, tubules with nuclei.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature shows conflicting results about the correlations of pulp changes incident to orthodontic force. Some reports suggested permanent damage to pulpal tissue from orthodontic force as tissue calcification and vascular alteration with vascular stasis and pulp necrosis [ 12 ] but others supported no significant long-lasting effects of dental pulp [ 13 , 14 ]. The clinical impact of these studies was to determine whether any alterations in pulpal tissues could affect the long-term vitality of the teeth.…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, Consolaro 8 described the tooth movement in 39 rats, with periods of 1 to 7 days, using the model initially developed by Heller and Nanda, 9 recognized worldwide as the most employed in studies on this subject. The study analyzed pulp tissues, 8 , 10 compared to those of teeth of other 9 animals not submitted to tooth movement. It was concluded that induced tooth movement did not promote morphological alterations in the dental pulp detectable by light microscopy, either degenerative or inflammatory.…”
Section: Two Examples Of Morphological Evidences In Humans and Animalmentioning
confidence: 99%